Immunity comes first: The effect of parasite genotypes on adaptive immunity and immunization in three-spined sticklebacks. Issue 1 (January 2016) - Haase, David; Rieger, Jennifer K.; Witten, Anika; Stoll, Monika; Bornberg-Bauer, Erich; Kalbe, Martin; Reusch, Thorsten B.H.
Abstract: Adaptive immunity in vertebrates can confer increased resistance against invading pathogens upon re-infection. But how specific parasite genotypes affect the temporal transition from innate to adaptive immunity under continual exposure to parasites is poorly understood. Here, we investigated the effects of homologous and heterologous exposures of genetically distinct parasite lineages of the eye fluke Diplostomum pseudospathaceum on gene expression patterns of adaptive immunity in sticklebacks ( Gasterosteus aculeatus ). Observable differences in gene expression were largely attributable to final exposures while there was no transcription pattern characteristic for a general response to repeated infections with D. pseudospathaceum. None of the final exposure treatments was able to erase the distinct expression patterns resulting from a heterologous pre-exposed fish. Interestingly, heterologous final exposures showed similarities between different treatment groups subjected to homologous pre-exposure. The observed pattern was supported by parasite infection rates and suggests that host immunization was optimized towards an adaptive immune response that favored effectiveness against parasite diversity over specificity. Highlights: We analyzed the transcriptome of sticklebacks exposed to different parasite genotypes. A clustering of complement genes could be observed in head kidney samples. Genotype of final infection was not essential to immune response. Adaptive immune responses most likely optimized for genotype-independent resistance.